2021
DOI: 10.1002/humu.24245
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for de novo variants in SYNCRIP as the cause of a neurodevelopmental disorder

Abstract: SYNCRIP encodes for the Synaptotagmin‐binding cytoplasmic RNA‐interacting protein, involved in RNA‐binding and regulation of multiple cellular pathways. It has been proposed as a candidate gene for neurodevelopmental disorders (NDDs) with autism spectrum disorder (ASD), intellectual disability (ID), and epilepsy. We ascertained genetic, clinical, and neuroradiological data of three additional individuals with novel de novo SYNCRIP variants. All individuals had ID. Autistic features were observed in two. One in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Furthermore, several pathogenicity scores could significantly discriminate between MVA subtypes and healthy individuals [23] . Additionally, the aRgus workflow could identify protein regions within functional domains that appear to be especially important in pathogenesis of a SYNCRIP -associated neurodevelopmental disorder and a gluconeogenesis defect caused by phosphoenolpyruvate carboxykinase deficiency [24] , [25] . For the latter two genes, this analysis was pivotal as only few disease-related variants had been previously reported and knowledge derived from the aRgus model might support future variant interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several pathogenicity scores could significantly discriminate between MVA subtypes and healthy individuals [23] . Additionally, the aRgus workflow could identify protein regions within functional domains that appear to be especially important in pathogenesis of a SYNCRIP -associated neurodevelopmental disorder and a gluconeogenesis defect caused by phosphoenolpyruvate carboxykinase deficiency [24] , [25] . For the latter two genes, this analysis was pivotal as only few disease-related variants had been previously reported and knowledge derived from the aRgus model might support future variant interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently have the studies begun to uncover the behavioral functions of SYNCRIP. An animal model study showed that SYNCRIP controls starvation-induced hyperactivity in drosophila 64 , while a case report proposed that de novo variants in SYNCRIP is linked to neurodevelopmental disorders 65 . However, the association between SYNCRIP and behavioral functions as well as dysfunctions remains largely unclear to date.…”
Section: Discussionmentioning
confidence: 99%
“…Top family members have been reported to facilitate transcription of long genes linked to autism (King et al, 2013). Syncrip (−1.4) (SFARI list) (also known as Hnrnpg) encodes the synaptotagmin-binding cytoplasmic RNA-interacting protein, which is a candidate gene for ASD and ID (Rauch et al, 2012;Lelieveld et al, 2016;Semino et al, 2021). Bannai et al (2004) reported that Syncrip is a component of mRNA-containing granules in dendrites, possibly regulating local protein synthesis in developing dendritic spines.…”
Section: Examination Of Tablesmentioning
confidence: 99%